Anemia and Bone Marrow Suppression after Intra-Arterial Chemotherapy in Children with Retinoblastoma - SIRAJ NABI,; SAYED ALI,; AMIR ZEB KHAN,; MARIUM NADEEM KHAN,; GEETA KUMARI, (Pakistan Journal of Medical & Health Sciences, 2025)
Background: Intra-arterial chemotherapy (IAC) has become a vital treatment approach for retinoblastoma, particularly in cases where other therapies have failed. Objective: This study investigates the incidence, severity, and factors influencing anemia and bone marrow suppression in children with retinoblastoma undergoing IAC. Methods: This retrospective study was conducted at Pediatrics Department, Swat Medical College & Swat Medical Complex Teaching Hospital Saidu Sharif Swat during January 2024 to August 2024. A total of 185 pediatric patients who underwent IAC treatment for retinoblastoma were included in this study. Patients aged 0 to 18 years who had received at least one cycle of IAC as part of their treatment regimen for retinoblastoma were included in the study. Patients who had incomplete medical records or were lost to follow-up were excluded from the study. Results: The incidence of anemia increased from 10% before IAC to 65% after treatment. Bone marrow suppression was observed in 55% of patients, with severe neutropenia and thrombocytopenia occurring in 15% and 10%, respectively. The number of IAC cycles (≥5) and the dose of melphalan were significant predictors of anemia and bone marrow suppression severity (p < 0.01). Advanced-stage disease was also associated with a higher risk of severe hematologic toxicity (p < 0.05). Supportive care interventions, such as blood transfusions and granulocyte colony-stimulating factor (G-CSF), were effective in managing these complications. Conclusion: Anemia and bone marrow suppression are common complications in children with retinoblastoma undergoing IAC.